Molecular identification of ovine Theileria species by a new PCR-RFLP method - Bami, M. Heidarpour; Haddadzadeh, H. R.; Kazemi, B.; Khazraiinia, P.; Bandehpour, M.; Aktas, M. (Elsevier Science Bv, 2009)
Theileria spp. infect wild and domestic ruminants in the tropical and subtropical regions of the world. Two species, T. lestoquardi and T. ovis, are suspected to cause ovine theileriosis in Iran. The epidemiological aspects of ovine theileriosis in Iran are poorly understood, and further investigations by sensitive and precise techniques are required. In this study, the use of a nested PCR for amplification of a fragment of the 18S ribosomal DNA from virtually all species of Theilerla is described. For differentiation of various Theileria spp. a RFLP assay was developed as a diagnostic tool enabling direct, concurrent, highly specific and sensitive identification of Theileria spp. The sensitivity of the nested PCR for Theileria species was 10(-5)% parasitemia. Restriction fragment length polymorphism (RFLP) of the PCR products allowed differentiation between three different Theileria species (T. annulata, T. lestoquardi and T. ovis) and seems to be useful for differentiation of other species such as T. separata and Theileria spp. china. From 100 field blood samples obtained from sheep in East and South-East Iran, 56% were positive for Theilerla spp. by nested-PCR compared with 21% by microscopic examination. Out of 56 positive samples, 12.5% (7/56) were positive for T. ovis and 87/5% (49/56) were positive for T. lestoquardi. This is the first report in which T. ovis has been detected in Iran using molecular identification techniques. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ovine theileriosis; Molecular identification; Theileria ovis; Theileria lestoquardi; Iran